PENYELESAIAN KREDIT MACET PADA PT FEDERAL INTERNASIONAL FINANCE (FIF) BERDASARKAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 - Muchamad Taufiq Hidayat (Journal of Innovation Research and Knowledge, 2025)
PT Federal Internasional Finance (PT FIF) is an institution established by the Minister of Finance engaged in leasing, factoring, and consumer financing and its own bank financial institution which is used to provide credit guarantee services using the system determination in Law No. 42 of 1999 Article 15 paragraph (2) concerning Fiduciary Guarantees. The purpose of this study is to analyze the application of credit agreements and settlements in the event of bad debts at PT FIF according to Law No. 42 of 1999. The type of research used by the author is the Juridical Sociological research type. Respondents in this study were customers of PT. Federal Internasional Finance, who were selected because of their relevant roles and contributions to the data needed to achieve the research objectives. The data analysis technique used Qualitative Descriptive. The results of this study indicate that (1) PT FIF has implemented credit provision with collateral and default settlement in accordance with the provisions stipulated in Law No. 42 of 1999 concerning Fiduciary Guarantees; (2) Settlement in the event of bad debt occurs through several stages, namely: Communication and Negotiation. PT Federal Internasional Finance prioritizes the importance of communication and negotiation in the debt settlement process, contacting customers who are experiencing difficulties in paying through desk collection, involving payment rescheduling, the settlement stage if it fails, and unit execution.